Optogenetic silencing of locus coeruleus activity in mice impairs cognitive flexibility in an attentional set-shifting task - Janitzky, Kathrin; Lippert, Michael T.; Engelhorn, Achim; Tegtmeier, Jennifer; Goldschmidt, Jürgen; Heinze, Hans-Jochen; Ohl, Frank W. (Frontiers in Behavioral Neuroscience, 2015)
The locus coeruleus (LC) is the sole source of noradrenergic projections to the cortex and essential for attention-dependent cognitive processes. In this study we used unilateral optogenetic silencing of the LC in an attentional set-shifting task (ASST) to evaluate the influence of the LC on prefrontal cortex-dependent functions in mice. We expressed the halorhodopsin eNpHR3.0 to reversibly silence LC activity during task performance, and found that silencing selectively impaired learning of those parts of the ASST that most strongly rely on cognitive flexibility. In particular, extra-dimensional set-shifting (EDS) and reversal learning was impaired, suggesting an involvement of the medial prefrontal cortex (mPFC) and the orbitofrontal cortex. In contrast, those parts of the task that are less dependent on cognitive flexibility, i.e. compound discrimination (CD) and the intra-dimensional shifts (IDS) were not affected. Furthermore, attentional set formation was unaffected by LC silencing. Our results therefore suggest a modulatory influence of the LC on cognitive flexibility, mediated by different frontal networks.